Elemental analysis (TC, TOC, IC) and X-Ray diffraction (XRD) data from sediment core PS72/410-3 (Mendeleev Ridge, Arctic Ocean) - Isabell Schulte-Loh; Ruediger Stein (PANGAEA, 2025)
On a 700 km long transect at about 80° 30 extquotesingle N from the Canada Basin across the central Mendeleev Ridge into the Makarov Basin 10 sediment cores were retrieved during Polarstern Expedition PS72 (Jokat, 2009), including Core PS72/410-3 (80°31.38 extquotesingleN, 175°43.26 extquotesingleW; 1808 m water depth). The predominent lithology is silty clay (to sandy silty clay) of brown to dark brown, light to dark yellowish brown, and light olive brown colours. In the upper about 3.8 m, more sandy intervals, dropstones, and mud clasts occur (Stein et al., 2009). The most prominent features of all cores recovered on the PS72 transect across Mendeleev Ridge are colour cycles of brown to dark brown and light olive brown to yellowish brown sediments occurring down to the bottom of the cores, and specific marker horizons (i.e., pink-white and white layers). Based on the visual core description, the standard lithological units A to M developed by Clark et al. (1980) using several hundred of short sediments cores collected from Ice Island T-3 (or Fletcher extquotesingles Ice Island) in the Amerasian Basin, could also be identified in the PS72 sediment cores from the central Mendeleev Ridge transect as well. Following Clark et al. (1980), the content of sand-sized material (enriched in units C, F, H, J, L, and parts of M) and the pink-white (dolomite-rich) layers were considered to be the key sedimentary characteristic used for correlation of these lithostratigraphic units and indicative for input ice-rafted debris (IRD) during tims of extended glaciations (Stein et al., 2009, 2010a, 2010b). This very specific coarse-grained and dolomite-rich lithology can be related to a restricted source area in the Canadian Arctic (Bank Island, Victoria Island) where Paleozoic carbonates (dolomite) are cropping out, and it can be interpreted as pulses of increased iceberg discharge due to the disintegration of extended Canadian glacial ice sheets (e.g., Clark et al., 1980; Vogt, 1997; Phillips and Grantz, 2001; Stein et al., 2010a, 2010b). Elemental analysis and X-Ray diffraction (XRD) measurements were carried-out at the Alfred Wegener Institute by Isabell Schulte-Loh as part of her Master Thesis (Schulte-Loh, 2010). For the measurement of bulk parameters by means of elemental analysis, freeze-dried and homogenized sediments were used. Total organic carbon (TOC) contents were measured by Carbon-Sulfur Analyser (CS-125, Leco) after removing carbonate with hydrochloric acid. Total carbon (TC) contents were determined by Carbon-Nitrogen-Sulfur Analyser (Elementar III, Vario). Inorganic (carbonate) carbon (IC) was calculated as IC = TC-TOC. In order to reconstruct the detrital sediment provenance, transport processes and ice-sheet history, X-Ray diffraction (XRD) analyses were carried-out using ground bulk sediment (Stein et al., 2010a). The relative contents of the determined minerals are expressed as relative peak intensities. Based on XRD data determined on a selected set of samples, the major proportion of the inorganic carbon is related to dolomite and calcite whereas aragonite and siderite only occur in very, very minor amounts. Thus, for getting a first-order estimate of the detrital carbonate (dolomite), the inorganic carbon was simply divided into its calcite and dolomite proportions using the relative intensity values of the calcite (3.04 Å) and dolomite (2.89 Å) XRD peaks and assuming that calcite plus dolomite equals to the total carbonate content (IC) (for details and calculation procedure see Stein et al., 2010a).